Hidronefrosis y patologías asociadas. - Fernández Montarroso, L.; Jiménez Penick, F.J.; Mazuecos López, M.P.; Mohamed Mohamed-abdallah, Z.; Resel, Luis; San José Mansó, L.; Bocardo Fajardo, Gloria (Clínicas Urológicas de la Complutense, 2002)
Sin resumen